2011
DOI: 10.1007/s10464-011-9431-4
|View full text |Cite
|
Sign up to set email alerts
|

Unikkaartuit: Meanings of Well‐Being, Unhappiness, Health, and Community Change Among Inuit in Nunavut, Canada

Abstract: Suicide among young Inuit in the Canadian Arctic is at an epidemic level. In order to understand the distress and well-being experienced in Inuit communities, a first step in understanding collective suicide, this qualitative study was designed. Fifty Inuit were interviewed in two Inuit communities in Nunavut, Canada, and questionnaires asking the same questions were given to 66 high school and college students. The areas of life investigated here were happiness and wellbeing, unhappiness, healing, and communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
196
1
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 160 publications
(209 citation statements)
references
References 52 publications
4
196
1
8
Order By: Relevance
“…These kinds of generalized assessments provide only a narrow understanding of Indigenous well-being (Prout 2011;Kral et al 2011;Parlee et al 2007). Well-being, like the .…”
Section: Theoretical Framework: Concepts Of Well-being-what Does It Mmentioning
confidence: 99%
“…These kinds of generalized assessments provide only a narrow understanding of Indigenous well-being (Prout 2011;Kral et al 2011;Parlee et al 2007). Well-being, like the .…”
Section: Theoretical Framework: Concepts Of Well-being-what Does It Mmentioning
confidence: 99%
“…A study conducted in Sweden found that young Sami experienced a higher prevalence of suicidal expressions and suicide in significant others but not a higher prevalence of suicide attempts compared to young Swedes (Omma, Sandlund, & Jacobsson, 2013). Kral, Idlout, Minore, Dyck, and Kirmayer (2011) found in their study on the meaning and experience of well-being among Inuit in Nunavut (Canada) that respondents experienced suicide as a major social problem. Here, respondents, among these also suicide attempters, identified romantic relationship problems and family problems as the trigger for most youth suicides (Kral et al, 2011).…”
Section: Mixed Methodsmentioning
confidence: 84%
“…Kral, Idlout, Minore, Dyck, and Kirmayer (2011) found in their study on the meaning and experience of well-being among Inuit in Nunavut (Canada) that respondents experienced suicide as a major social problem. Here, respondents, among these also suicide attempters, identified romantic relationship problems and family problems as the trigger for most youth suicides (Kral et al, 2011).…”
Section: Mixed Methodsmentioning
confidence: 99%
See 2 more Smart Citations